Mothering a Bodied Curriculum Emplacement, Desire, Affect - Freedman, Debra; Springgay, Stephanie (University of Toronto Press, 2018)
This collection considers how embodiment, mothering, and curriculum theory are related to practices in education that silence, conceal, and limit gendered, raced, and sexual maternal bodies. Advancing a new understanding of the maternal body, it argues for a 'bodied curriculum' – a practice that attends to the relational, social, and ethical implications of ‘being-with’ other bodies differently, and to the different knowledges such bodily encounters produce.Contributors argue that the prevailing silence about the maternal body in educational scholarship reinforces the binary split between domestic and public spaces, family life and work, one's own children and others' children, and women's roles as ‘mothers’ or ‘others.’ Providing an interdisciplinary perspective in which postmodern ideas about the body interact with those of learning and teaching, Mothering a Bodied Curriculum brings theory and practice together into an ever-evolving conversation